Methodological and strategic requirements for research in water and sustainability - The example of Akiz, a Vietnam-German flagship project for industrial zone wastewater management - Rudolph, Karl-Ulrich; Long, Nguyen Van; Ha, Mai; Cam, Bui Duy; Nam, Nguyen Van; Genthe, Wolfgang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Whenever research wants to contribute to the development and implementation of technology based solution in complex fields like water management, there are certain methodological and strategic requirements to be fulfilled. Basic research will remain the fundament. However, applied research is to follow, on output-oriented research objectives. Furthermore, there is need for "multi-bridging" between academia and industries, between research and education as well as between different disciplines (like technologies/engineering and management/economics). The exchange of know-how and collaboration between different countries, complementary to each others (like Germany and Vietnam) can be very fruitful. Finally, water research will have to be embedded in the overall context of sustainability. The article describes details and give the example of one project AKIZ - wastewater concepts for industrial zones, Tra Noc) to show, how these methodological and strategic requirements can be fulfilled.